Socioeconomic consequences of the 2004 tsunami: policy implications for natural disaster management - Tin, Tin Su; Saimy, B.I.; Bulgiba, Awang (Elsevier, 2013)
OBJECTIVE: The objective of the study is to assess the socioeconomic status of the households affected by the tsunami of 2004 & to determine the factors associated with the recovery of household economic status. METHODS: The study was conducted in tsunami-affected areas in Malaysia in 2010-2011. A total of 193 households were included in the survey. Multivariate logistic regression was performed to determine the factors related to the recovery of households' economic status. FINDINGS: Among 193 households, 37 were in a better condition, 40 were unchanged and 22 had not recovered. It took 2.2years to get back to pre-disaster economic status. Factors leading to successful household economic recovery were "household resided in Sungai Petani", "belong to highest income quartile" and "age of household head". In contrast, "extended family type" and "unemployed household head" reduced the odds of recovery. Households which lost their fishing boats during the tsunami had less chance to recover their previous status. CONCLUSION: The findings of our study would be useful for policy consideration and planning of post disaster management in order to enhance the recovery of household economic status in the short period.